Peningkatan Pengetahuan Masyarakat tentang Konsumsi Ikan melalui Program Gemarikan sebagai Upaya Pencegahan Stunting di Desa Banda Masen: Pengabdian - Cut Rozana Sari; Anis Nugrahawati; Nopri Yanto; Asih Makarti Muktitama; Rinaldi; Arina Ruzanna (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
Stunting remains a chronic nutritional problem and a major challenge in public health development in Indonesia. One of the contributing factors to stunting is the low intake of animal protein, particularly fish, due to limited public knowledge and dietary habits. This community service activity aimed to improve community knowledge and understanding of the importance of fish consumption as an effort to prevent stunting through the socialization of the Community Movement for Fish Consumption (Gerakan Masyarakat Makan Ikan/Gemarikan). The activity was conducted in Banda Masen Village, Lhokseumawe City, in June 2024, targeting community members, especially housewives and families with toddlers. The method applied an educational and participatory approach through lectures, interactive discussions, fish-processing demonstrations, and evaluation using pretest and posttest questionnaires. The results showed an increase in community knowledge across all assessed aspects, including understanding of stunting, nutritional content of fish, benefits of fish consumption, and healthy and attractive fish-processing methods. High community participation during the activity also indicated a positive response to the implemented program. Therefore, the socialization of Gemarikan proved to be effective in enhancing community nutritional knowledge and has the potential to support stunting prevention efforts at the community level.   Keywords: Community Movement for Fish Consumption, Lhokseumawe City, Stunting, Community Service